Characterizing source fingerprints and ageing processes in laboratory-generated secondary organic aerosols using proton-nuclear magnetic resonance (1H-NMR) analysis and HPLC HULIS determination - N. Zanca; N. Zanca; A. T. Lambe; A. T. Lambe; P. Massoli; M. Paglione; D. R. Croasdale; Y. Parmar; E. Tagliavini; S. Gilardoni; S. Decesari (Atmospheric Chemistry and Physics, 2017)
The study of secondary organic aerosol (SOA) in laboratory settings has greatly increased our knowledge of the diverse chemical processes and environmental conditions responsible for the formation of particulate matter starting from biogenic and anthropogenic volatile compounds. However, characteristics of the different experimental setups and the way they impact the composition and the timescale of formation of SOA are still subject to debate. In this study, SOA samples were generated using a potential aerosol mass (PAM) oxidation flow reactor using α-pinene, naphthalene and isoprene as precursors. The PAM reactor facilitated exploration of SOA composition over atmospherically relevant photochemical ageing timescales that are unattainable in environmental chambers. The SOA samples were analyzed using two state-of-the-art analytical techniques for SOA characterization – proton nuclear magnetic resonance (1H-NMR) spectroscopy and HPLC determination of humic-like substances (HULIS). Results were compared with previous Aerodyne aerosol mass spectrometer (AMS) measurements. The combined 1H-NMR, HPLC, and AMS datasets show that the composition of the studied SOA systems tend to converge to highly oxidized organic compounds upon prolonged OH exposures. Further, our 1H-NMR findings show that only α-pinene SOA acquires spectroscopic features comparable to those of ambient OA when exposed to at least 1  ×  1012 molec OH cm−3  ×  s OH exposure, or multiple days of equivalent atmospheric OH oxidation. Over multiple days of equivalent OH exposure, the formation of HULIS is observed in both α-pinene SOA and in naphthalene SOA (maximum yields: 16 and 30 %, respectively, of total analyzed water-soluble organic carbon, WSOC), providing evidence of the formation of humic-like polycarboxylic acids in unseeded SOA.